PENGUATAN PENDIDIKAN KARAKTER ANAK USIA DINI BERBASIS BUDAYA LOKAL KUA HORANG SEBUAH PANTUN PANEN PADI - Tabun, Norlianti Lusia; Maarang, Martheda; Lily, Netry Maria; Dony, Petrus Mau Tellu (Early Childhood: Jurnal Pendidikan, 2025)
This study aims to explore the character values contained in the traditional pantun "Kua Horang" and explore its implementation strategies in early childhood learning. The approach used is descriptive qualitative with a case study method. Data were obtained through interviews, observations, and documentation of PAUD teachers, traditional figures, and pantun texts. The results of the study indicate that the pantun "Kua Horang" contains character values such as responsibility, mutual cooperation, religion, discipline, respect for nature, perseverance and tenacity and politeness. Integration strategies into PAUD learning include role-playing activities, value discussions, art, and thematic projects. This study confirms that local wisdom can be used as an effective medium in shaping the character of early childhood in a contextual and enjoyable way.